Central and nephrogenic diabetes insipidus: updates on diagnosis and management - Flynn, Kathryn; Hatfield, Jennifer; Brown, Kevin; Vietor, Nicole; Hoang, Thanh (Frontiers in Endocrinology, 2025)
Diabetes insipidus (DI) is a rare endocrine disease involving antidiuretic hormone (ADH), encompassing both central and nephrogenic causes. Inability to respond to or produce ADH leads to inability of the kidneys to reabsorb water, resulting in hypotonic polyuria and, if lack of hydration, hypernatremia. DI cannot be cured and is an unfamiliar disease process to many clinicians. This diagnosis must be distinguished from primary polydipsia and other causes of hypotonic polyuria. The main branchpoints in pathophysiology depend on the level of ADH pathology: the brain or the kidneys. Prompt diagnosis and treatment are critical as DI can cause substantial morbidity and mortality. The gold standard for diagnosis is a water deprivation test followed by desmopressin administration. There is promising research regarding a new surrogate marker of ADH called copeptin, which may simplify and improve the accuracy in diagnosing DI in the future. Patients with DI require adequate access to water, and there are nuances on treatment approaches depending on whether a patient is diagnosed with central or nephrogenic DI. This article describes a stepwise approach to recognition, diagnosis, and treatment of DI.